Factors influencing the coach-athlete relationship in Malaysian team sports - Murugeesan, Yokananthini (2017)
Interpersonal communication plays a vital role in gaining success in sports. Literature concerning interpersonal communication between the coach and athlete in sports context is always mixed in its results in various countries due to the culture they live in. In Malaysia, literature concerning communication styles and culture (ethnicity) in influencing the coach and athlete relationship is sparse. This study fills the gap by exploring the factors influencing coach-athlete relationship. The purpose of this study is to understand the factors influencing the coach and athlete in Malaysian team sports. Specifically, on two main objectives, namely, how communication styles and culture (ethnicity) influence the coach and athlete relationship. Employing the interdependence theory by Thibaut and Kelley (1959), researcher used a qualitative approach in this study to explore the complexities and multifaceted levels of understanding among elements such as communication styles and culture which are embedded in a given social context. A semi-structured interview guide was developed based on the relevant literature and theories. Six key informants were chosen based on purposive sampling. Two athletes from synchronised swimming and two athletes from football, also coaches from these two sports that are staying in hostels at National Sports Council. Researcher chose an interpretive (constructivist) approach of interpreting the data. Results report that key informants (athlete) are submissive and introvert at the same time. Key informants (coaches) are assertive; they do not display authoritative approach towards athletes, they are stern in giving instructions. Throughout the study, age factor emerged as an issue that could play a role in building relationship. Results indicate that cultural (ethnicity) may not be as critical as may be assumed an issue in building the relationship between coach and athlete in Malaysia. Cultural tolerance among the key informants revealed to be the key role in the quality of the coach-athlete relationship. This study is significant in developing a quantitative instrument in the future based on the tentative models of this research. Also, practitioners are more likely to provide more communication opportunities for both coaches and athletes to act pro-social to achieve good relationship.